The Mediatization of Eco-Islam in Environmental Communication: A Systematic Literature Review of Narratives, Actors, and Media - Ilah Holilah; Eneng Purwanti; Khairil Anam (Fakultas Dakwah dan Komunikasi UIN Sunan Gunung Djati Bandung Sunan Gunung Djati Bandung, 2025)
The global environmental crisis demands a communication approach that is not solely technocratic but also rooted in society's moral and cultural values . In Muslim societies, Eco-Islam offers a relevant theological-ethical framework, but previous studies tend to emphasize normative aspects and local practices, while the media's role in shaping and disseminating Eco-Islamic narratives remains understudied. This study aims to analyze the construction and representation of Eco-Islamic narratives in environmental communication, identify the actors and media involved, and evaluate the challenges and strategies of media communication in academic literature. The method used is a Systematic Literature Review (SLR) in accordance with the PRISMA 2020 guidelines. A search was conducted in Scopus and Google Scholar databases for English-language open-access journal articles published between 2017 and 2025. Of the 276 initial documents, 20 articles were analyzed using thematic content analysis. The results show the dominance of the values of Tawhid, Khilafah, and Amanah mediated through religious and digital media, but they are still normative and do not encourage changes in ecological behavior. This study enriches studies of environmental communication through media and religion and offers strategic implications for the development of more transformative Eco-Islamic communication